The Delicate Balance to Adjustment: A Qualitative Approach of Student's Transition to the First Year at University. Issue 1 (27th April 2018) - De Clercq, Mikaël; Roland, Nathalie; Brunelle, Magali; Galand, Benoit; Frenay, Mariane
First year experience in higher education has been extensively investigated in the literature. Yet, two limitations can be identified out of the literature. The majority of the studies focused on single factor analysis, restraining the multifactorial understanding of adjustment's determinants. Moreover, the temporal unfolding of the first year at the university has mainly been disregarded, limiting the dynamic framing of adjustment process. To overcome these limitations, the current study used a longitudinal qualitative design in order to grasp the dynamic complexity of adjustment process. Semi-structured interviews were conducted in two steps with 17 freshmen from Science department. The aims were to unfold the constructs at play in student's adjustment process and the dynamic interplay between them over time. The analyses were grounded into Nicholson's theoretical framework of transition cycle and the material was analyzed through thematic and sequential analysis. Four themes ( readiness, reaching personal drives, fighting an overwhelming program and becoming a self-regulated learner ) and four different events ( starting up, click, exhaustion and deficiencies accumulation ) were identified in the material disclosing the dynamic nature of adjustment process. An overall reflection on the findings is proposed in the conclusion.